Increasing Work Productivity through Achieving Work Standardization, Satisfaction and Work Motivation of Baznas Yogyakarta Employees - Hidayati, Hidayati; Nuvriasari, Audita (Asian Journal of Community Services, 2024)
This internship report discusses the Improvement of Work Productivity Through the Achievement of Work Standardization, Satisfaction and Work Motivation of Amil Baznas Yogyakarta. Baznas Yogyakarta City has an inadequate number of Human Resources. So that it causes overlapping work which causes the work to not be completed effectively and efficiently. The method used in this internship report activity is to use the interview method, observation, counseling, and field practice. The concept used in this study is the Robbins & Judge concept of performance effectiveness motivation includes three important elements, namely intensity, direction, and persistence. The results of this internship are carried out internship activities, increasing work motivation and employee motivation counseling, internship activity interviews, and employee performance satisfaction evaluation.